2006
DOI: 10.1002/jso.20498
|View full text |Cite
|
Sign up to set email alerts
|

Isolated lung perfusion with melphalan: Pharmacokinetics and toxicity in a pig model

Abstract: This study on pigs proved to be a well reproducible model for ILP with melphalan. Pharmacokinetics show a safety profile with no systemic toxicity, which could justify further patient studies, necessary to determine its effect on pulmonary metastases in humans, especially in case of adjuvant therapy after surgical resection or in unresectable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In another study, pigs submitted to IVLP with and without chemotherapy demonstrated higher histologic injury scores and impairment of functional parameters compared with a sham group. 16 Histologic signs of hemorrhagic edema were found in both the control and melphalan-treated groups, 17 raising the question of the potential role that the perfusion circuit may have in causing injury. More recently, Pages and colleagues 18 performed IVLP for 30 minutes in 50-kg pigs, with a perfusion flow that ranged from 500 to 600 mL/min (adjusted to a PA pressure of around 25 mm Hg) and found that the control group had even greater histologic injury compared with lungs perfused with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, pigs submitted to IVLP with and without chemotherapy demonstrated higher histologic injury scores and impairment of functional parameters compared with a sham group. 16 Histologic signs of hemorrhagic edema were found in both the control and melphalan-treated groups, 17 raising the question of the potential role that the perfusion circuit may have in causing injury. More recently, Pages and colleagues 18 performed IVLP for 30 minutes in 50-kg pigs, with a perfusion flow that ranged from 500 to 600 mL/min (adjusted to a PA pressure of around 25 mm Hg) and found that the control group had even greater histologic injury compared with lungs perfused with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first and only reported study showing the additional effects of two chemotherapeutic agents in the setting of ILuP and it is a promising tool for future phase I clinical studies. The pharmacokinetic properties of ILuP with melphalan have also been investigated in a pig model, demonstrating its feasibility, safety and the absence of any systemic toxicity (159).…”
Section: Melphalanmentioning
confidence: 99%
“…Pharmacokinetics of melphalan were further investigated in a pig model by van der Elst et al demonstrating a safe pharmacokinetic profile without systemic toxicity [45].…”
Section: Melphalanmentioning
confidence: 99%